2014
DOI: 10.1016/j.jtcvs.2013.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for infective endocarditis complicated by cerebral embolism: A consecutive series of 375 patients

Abstract: Survival after surgery for AIE is significantly impaired once cerebral embolism has occurred; however, it does not differ in patients with symptomatic versus silent cerebral embolism. Routine computed tomography scans are therefore mandatory due to the high incidence of asymptomatic cerebrovascular embolism--which appears to be equally as dangerous as symptomatic embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 24 publications
1
55
0
2
Order By: Relevance
“…Other studies have confirmed the association of these factors with worse prognosis. 1,13,14 A possible explanation for the dismal prognosis associated with non-HACEK Gram-negative bacilli endocarditis could that these microorganisms are healthcare-related agents. 15 Increasing age, 16 diabetes, 17 prosthetic valve involvement, 18 heart failure and paravalvular complications 13 have been identified in other studies as risk factors for higher mortality.…”
mentioning
confidence: 99%
“…Other studies have confirmed the association of these factors with worse prognosis. 1,13,14 A possible explanation for the dismal prognosis associated with non-HACEK Gram-negative bacilli endocarditis could that these microorganisms are healthcare-related agents. 15 Increasing age, 16 diabetes, 17 prosthetic valve involvement, 18 heart failure and paravalvular complications 13 have been identified in other studies as risk factors for higher mortality.…”
mentioning
confidence: 99%
“…Secondary outcome measures were; [10]. In order to find duplicates, all references were imported into Endnote where duplicates were removed.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The following search terms were used: 'treatment', 'extended treatment', 'continued treatment', 'rivaroxaban', 'Xarelto', 'dabigatran', 'Pradaxa', 'apixaban', 'Eliquis', 'vitamin K antagonist', 'warfarin', 'placebo', 'direct Xa inhibitor', 'direct thrombin inhibitor', 'oral anticoagulant', 'venous thromboembolism', 'deep venous thromboembolism' and 'pulmonaryembolism'. In Pubmed, the "Cochrane highly sensitive search filter for randomized clinical trials" was used[10]. In Embase search words for clinical trials were used with inspiration from the Cochrane…”
mentioning
confidence: 99%
“…Septic cerebral embolic events frequently occur in left-sided infective endocarditis (IE) with a reported incidence of clinically significant lesions in approximately 20–40% of patients (12). These lesions place patients at increased risk of morbidity and mortality compared with their counterparts who have not suffered an embolic event (34).…”
Section: Introductionmentioning
confidence: 99%
“…However, postoperative degeneration of preoperatively identified cerebral lesions has been found to be a fairly rare event (1, 1213). The combination of a low postoperative incidence of hemorrhagic stroke and the persistent risk of further embolization in medically treated endocarditis creates a strong argument to consider early surgical therapy.…”
Section: Introductionmentioning
confidence: 99%